PEMAHAMAN KARAKTERISTIK PERKEMBANGAN DAN AKTIVITAS PEMBELAJARAN BAGI ANAK USIA DINI PADA PENGASUH DI TAMAN PENITIPAN ANAK (TPA) BINTANG - Astrella Amanda; Weny Savitry S. Pand (MANASA, 2013)
Child daycare is an alternative nurturing that can be chosen by working parents. In child daycare, caregivers have an important role so they are expected to have knowledge of child development and child learning activities. This study aims to find out the knowledge of the child development and child learning activities of caregivers in TPA Bintang (pseudonyms). This research using quantitative method which applied Kuesioner Pemahaman Karakteristik Perkembangan Anak and Kuesioner Aktivitas Pembelajaran bagi Anak, and qualitative method that observed the environment and learning activities of seven caregivers and interviewed of four caregivers. The result conveyed that caregivers have a good knowledge of child development but not accordant with the knowledge of implementation of child learning activity. These results can be used to design an intervening program to improve the caregivers’ capacity in applying their knowledge to children learning activities.